Establishment of seed germination and micropropagation protocols for Senegalia nigrescens, a potential anti-virulent species. (3rd October 2018) - Bodede, Olusola; Shaik, Shakira; Moodley, Roshila
ABSTRACT: This study describes seed germination and micropropagation of Senegalia nigrescens, an economic, medicinal and nitrogen-fixing species of South Africa. Seeds of S. nigrescens were subjected to pre-sowing treatments including soaking in cold water for 24 h, sulphuric acid (H2 SO4 ) or hydrochloric acid (HCl) for 4, 8 and 12 min and mechanically scarifying seeds before sowing on Petri plates with wet filter paper. Mechanically-scarified seeds were also sown aseptically on a filter paper bridge, plain agar, ½ or full strength Murashige and Skoog (MS) basal medium. Single nodal explants from MS-derived seedlings were grown on MS media supplemented with 0.0, 0.5, 1.0 and 2.0 mg L −1 of benzylaminopurine (BAP) or kinetin (KIN) and a combination of 0.5 mg L −1 of BAP and KIN to investigate shoot multiplication. No significant differences were observed in the number of shoots produced across all treatments. However, the treatment containing 1.0 mg L −1 KIN produced a significantly higher shoot length (14.17 ± 5.20 mm) than 0.5, 1.0 and 2.0 mg L −1 BAP (7.67 ± 3.87, 6.75 ± 2.93 and 8.70 ± 3.56 mm, respectively). The highest rooting rate (16.7%) was obtained on ¼ strength MS supplemented with either indole-3-acetic acid (IAA) or indole-3-butyric acid (IBA) at concentrations 1.0 and 0.5 mg L −1, respectively. Rooted plantlets were successfully acclimatised with a 66.7% survival rate. The findings from this study would be of great benefit for the commercial propagation of S. nigrescens .